Review of the Method of Valuation of the SDR. (Policy Papers; Policy Paper ;, 2010)
This paper provides the basis for the quinquennial review of the method of valuation of the SDR, and the financial instruments used to determine the SDR interest rate. Under the governing Board decisions, the new SDR valuation and interest rate baskets would come into effect on January 1, 2011. The review examines developments during the 2005-09 period in the variables relevant to the SDR valuation. These variables include exchange rates, exports of goods, services and income, and reserve holdings. Data for exports of goods and services show China has become the third largest exporter among Fund members and monetary unions including Fund members. Nonetheless, indicators such as reserves and international banking and debt securities suggest that the currencies in the current SDR basket continue to predominate in international financial transactions, and these currencies also account for the bulk of global foreign exchange turnover. At this time, the Chinese renminbi would not appear to meet the criteria for being determined by the Fund to be a freely usable currency, which is also required for inclusion in the SDR basket.